Sociocultural Factors Influencing Students’ Reluctance to Participate in Speaking Classes at Halu Oleo University - La Ode Malik Nur; Hanna Hanna; Aderlaepe Aderlaepe (Halu Oleo University, 2023)
This study aimed to describe and analyze the socio-cultural factors influencing students' reluctance to participate in speaking classes in the English Education Department at Halu Oleo University, specifically those enrolled in 2018. A qualitative research design was employed. The respondents were nine fifth-semester students from the English study program who were taking Speaking III. Data was collected through interviews to understand the students' reluctance to speak in class. The interview data was analyzed using the Miles and Huberman analysis technique, which includes data reduction, data presentation, and drawing conclusions (verification). The study found that students' reluctance to participate in speaking classes was influenced by several socio-cultural factors: willingness to volunteer, the presence of juniors and seniors, the lecturer's method of delivering material, campus interactions, and home environment interactions. Consequently, students' willingness to volunteer in speaking classes is shaped by their understanding of the material, fear of judgment, lecturer engagement, casual campus interactions, and limited exposure to English at home.